SSA AND THE PRESENT STATUS OF ELEMENTARY EDUCATION OF VISUALLY IMPAIRED CHILDRENENROLMENT, SPECIAL TEACHERS, BRAILLE TEXTBOOKS, ASSISTIVE DEVICES, ACCEPTING ENVIRONMENT : INCLUSIVE EDUCATION - Soni, R.B.L. (THE PRIMARY TEACHER, 2011)
Elementary education, which lays a foundation for life-long learning, is equally important for children with visual impairments. The major objective of Sarva Shiksha Abhiyan (SSA) and Right to Education (RTE) Act is to universalise elementary education (UEE). One of the major thrust areas of SSA therefore is on inclusion or mainstreaming Children with Special Needs (CWSN) into the fabric of formal elementary schooling. The coverage of Children with Special Needs (CWSN) in 2008-09 was 27.80 lakh (91.39%), out of which 20.36% visually impaired children were enrolled in Classes I-VIII, suggesting that greater attention is needed to bring these children into schools to achieve the goal of SSA. As far as special teachers, Braille textbooks, assistive devices are concerned, the situation is not satisfactory. There is a need for an independent evaluation of the programme to assess educational benefits accruing to different categories of disabled children, particularly children with visual impairments, whose educational and other needs are different from children with locomotor handicaps.